SOSIALISASI PEMBERIAN SENAM PADA IBU HAMILUNTUK MEMBANTU MEMPERMUDAH PROSES PERSALINAN YANG AMAN DI YAYASAN RUMAH TUMBUH HARAPAN BANDUNG - Ika Rahman; Ananta Hasbi Syah Bani Shabiran; Darwati Darwati; Lingga Agustina (Insight Power (Kekuatan Wawasan), 2022)
Pregnancy is an event that begins with conception (fertilization) and ends with the onset of labor. Pregnancy is a change to continue offspring that occur naturally and produce a fetus that grows in the mother's womb. Pregnancy causes physiological changes in pregnant women. During pregnancy, there are changes in almost all maternal systems and organs. The percentage of discomfort that appears in pregnant women is 20% leg swelling, 10% leg cramps, 60% shortness of breath, 20% headache, and 70% back pain. A mother's psychological changes will change in each trimester. Changes in the mother's psychological condition occur due to the increase in the hormone progesterone during pregnancy. Pregnancy anxiety 21% of pregnant women have clinical symptoms of anxiety and 64% will continue in the puerperium. Pregnancy exercise is an important method to maintain or improve the physical balance of pregnant women to facilitate a safe delivery process. The purpose of this pregnancy exercise is so that pregnant women can facilitate a safe delivery process. As a result of this activity, pregnant women are very enthusiastic about participating in and hearing the education provided by the committee. 10 pregnant women participated in this activity, but when the pregnancy exercise was taking place 3 people felt tired, then the committee instructed the pregnant women to rest and do breathing exercises. While the other 7 pregnant women continued to carry out pregnancy exercises with enthusiasm.Keywords: Pregnant women, Pregnancy exercise, Labor process.